2013
DOI: 10.1016/j.mce.2012.12.029
|View full text |Cite
|
Sign up to set email alerts
|

POD-1 binding to the E-box sequence inhibits SF-1 and StAR expression in human adrenocortical tumor cells

Abstract: Pod-1/Tcf21 is expressed at epithelial-mesenchymal interaction sites during development of many organs. Different approaches have demonstrated that Pod-1 transcriptionally inhibits Sf-1/NR5A1 during gonadal development. Disruption of Sf-1 can lead to disorders of adrenal development, while increased dosage of SF-1 has been related to increased adrenal cell proliferation and tumorigenesis. In this study, we analyzed whether POD-1 overexpression inhibits the endogenous Sf-1 expression in human and mouse adrenoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
42
3
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(59 citation statements)
references
References 29 publications
(40 reference statements)
11
42
3
3
Order By: Relevance
“…The finding that TCF21 can bind and inhibit the SF1 promoter (Franca et al, 2013; Tamura et al, 2001) provides a molecular explanation for the observed SF1 repression, although we cannot exclude that additional, Tcf21 -independent mechanisms may also contribute to the observed phenotype. Consequently WT1 appears to have a dual function in the development of the adrenal cortex.…”
Section: Discussionmentioning
confidence: 88%
“…The finding that TCF21 can bind and inhibit the SF1 promoter (Franca et al, 2013; Tamura et al, 2001) provides a molecular explanation for the observed SF1 repression, although we cannot exclude that additional, Tcf21 -independent mechanisms may also contribute to the observed phenotype. Consequently WT1 appears to have a dual function in the development of the adrenal cortex.…”
Section: Discussionmentioning
confidence: 88%
“…We used Tcf21 +/LacZ knock-in mice to characterize the temporal and spatial activity of the Tcf21 promoter in the mouse adrenal gland (França et al, 2013;Quaggin et al, 1999;Shibata et al, 2003). Although the hormonal profile has not been examined, heterozygous Tcf21 +/LacZ mice are expected to have normal adrenal function as they are viable, fertile and show no symptoms of adrenal hormone deficiencies.…”
Section: Tcf21 Is Expressed In the Adrenal Capsule And Its Expressionmentioning
confidence: 99%
“…After separation of the individual adrenal primordia (AP, fetal adrenal gland) and gonadal primordial (GP) from the shared adrenogonadal primordia (AGP), mesenchymal cells migrate and encapsulate the fetal adrenal gland between E11.5 and E12.5 in mice (Else and Hammer, 2005;Keegan and Hammer, 2002) or the 8th to 9th week of gestation in humans (França et al, 2013). The molecular mechanisms involved in this process are not well understood but the capsule has long been characterized as a simple structure that surrounds the gland.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple copies of SF-1 (NR5A1) gene stimulate tumour development [63]. A study focusing on the SF-1 inhibitor, Pod-1 (capsulin, epicardin, Tcf21), established that the TCF21 gene is down-regulated in ACCs, compared with ACAs and normal tissue [64]. SF-1 over-expression is much more significant in childhood than in adult ACTs.…”
Section: Steroidogenic Pathwaymentioning
confidence: 99%
“…Zwielokrotnienie liczby kopii genu SF-1 (NR5A1) stymuluje nowotworzenie [63]. Badania inhibitora SF-1, Pod-1 (capsulin, epicardin, Tcf21), wykazały, że gen TCF21 jest zahamowany w ACC, ale nie w ACA i normalnej tkance [64]. Nadekspresja SF-1 jest o wiele bardziej znacząca w nowotworach u dzieci niż u dorosłych.…”
Section: Prace Poglądoweunclassified